2014
DOI: 10.2320/matertrans.m2014167
|View full text |Cite
|
Sign up to set email alerts
|

Morphologies of Some Graphites in Ductile Cast Irons

Abstract: The internal structure of different types of graphite commonly found in the ductile cast iron were investigated by TEM technique for TEM samples prepared by FIB method to understand their nucleation and growth. Spheroidal and vermicular graphite were observed in the ductile cast iron with spheroidizing treatment. Flake graphite was observed in the same cast iron without the spheroidizing treatment. The spheroidal graphite had a three-fold internal structure, with an amorphous-like central region, annual rings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 8 publications
(4 reference statements)
4
7
0
Order By: Relevance
“…The SAED patterns in the inner zone are oblong which indicates that graphite got deformed during the casting process. Similar oblong rings to those reported here may be seen in the work by Hara et al [28] The most probable cause for this is when the liquid around the graphite nodules solidified in the metastable system as this is related to a contraction of about 4 to 5 pct. [29] Such a contraction leads to graphite nodules being stressed in compression.…”
Section: Discussionsupporting
confidence: 88%
“…The SAED patterns in the inner zone are oblong which indicates that graphite got deformed during the casting process. Similar oblong rings to those reported here may be seen in the work by Hara et al [28] The most probable cause for this is when the liquid around the graphite nodules solidified in the metastable system as this is related to a contraction of about 4 to 5 pct. [29] Such a contraction leads to graphite nodules being stressed in compression.…”
Section: Discussionsupporting
confidence: 88%
“…This confirm early TEM work on lamellar graphite [24]. More recent TEM work by Hara et al [25] also concluded that the internal structure of flake graphite consisted of thin layers of graphite platelets arranged in a "mosaic-like" structure, which is the tiled-roof configuration.…”
Section: Graphite Produced Through Liquid-solid Transformationsupporting
confidence: 85%
“…Randomly orientated graphite, with a hexagonal rather than rhombohedral structure, is located in the interplatelet areas. Hara et al [25] concluded that SG has a three-fold internal structure, with and amorphous central region, annular rings of a layered intermediate region, and a mosaic-like (tiled-roof) outer region made of large polygonal crystalline platelets. Recent TEM work by Theuwissen et al [31], argues that both flake and spheroidal graphite consist of blocks stacked upon each other that grow mainly by a 2D nucleation mechanism.…”
Section: Graphite Produced Through Liquid-solid Transformationmentioning
confidence: 99%
“…However, the problem of producing vermicular cast iron is difficult to control the vermicular graphite ratio. During the production process, in order to avoid a lot of flake graphite arising from lack modification and too much nodular graphite due to excessive modification, 3) there is a need to quickly and accurately detect the vermicular graphite ratio, and thus adjust the quantity of the vermicular agent in time.…”
Section: Introductionmentioning
confidence: 99%